High-resolution mapping of a complex disease, a model for rheumatoid arthritis, using heterogeneous stock mice. - Ahlqvist, E; Ekman, D; Lindvall, T; Popovic, M; Förster, M; Hultqvist, M; Klaczkowska, D; Teneva, I; Johannesson, M; Flint, J; Valdar, W; Nandakumar, K; et al. (2011)
Resolving the genetic basis of complex diseases like rheumatoid arthritis will require knowledge of the corresponding diseases in experimental animals to enable translational functional studies. Mapping of quantitative trait loci in mouse models of arthritis, such as collagen-induced arthritis (CIA), using F(2) crosses has been successful, but can resolve loci only to large chromosomal regions. Using an inbred-outbred cross design, we identified and fine-mapped CIA loci on a genome-wide scale. Heterogeneous stock mice were first intercrossed with an inbred strain, B10.Q, to introduce an arthritis permitting MHCII haplotype. Homozygous H2(q) mice were then selected to set up an F(3) generation with fixed major histocompatibility complex that was used for arthritis experiments. We identified 26 loci, 18 of which are novel, controlling arthritis traits such as incidence of disease, severity and time of onset and fine-mapped a number of previously mapped loci.